Social mobility of science and technology human resource in Asean countries - Nam, Nguyen Thanh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
The social mobility of science and technology (S&T) human resource in each field, in each country and region has different characteristics. But in the end, it is the problem of "brain drain" and "brain attraction", policy is the tool to solve that existing problem. There should be policies to promote social mobility of S&T human resource to encourage the flow of knowledge, especially the tacit knowledge between the research area at research institutes and universities and the production sector. The paper provides an initial picture of the current social mobility of S&T human resources in ASEAN countries and in-depth study of Thailand’s case in developing a talent social mobility program. From there, some suggestive recommendations will be drawn for countries in the ASEAN region, including Vietnam, on the policy of promoting social mobility of S&T human resources in the context of international and regional integration. Code: 20072701